A novel FPGA implementation of mirror-paradigm RS-based QC-LDPC decoder for NVM channels - Lim, Melvin Heng Li (2013)
The scrutiny of the class of Reed-Solomon (RS) based quasi-cyclic (QC) low-density parity-check (LDPC) codes has inspired the authors to propose a memory efficient mirror-paradigm (MP) RS-based QC-LDPC code by exploiting the geometrical properties from the RS-based QC-LDPC nomenclature. Without any loss in performance, the proposed MPRS-based QC-LDPC code delivers discernible memory savings that address the concerns of hefty H-matrices associated to lengthy codewords for non-volatile memory (NVM) applications. Besides, the MPRS-based QC-LDPC codes are not confined to any particular hardware implementation and are compatible with various decoder architectures to complement other optimization schemes.